A puzzle over several decades: eye anomalies with FRAS1 and STRA6 mutations in the same family. (20th February 2012) - Ng, WY; Pasutto, F; Bardakjian, TM; Wilson, MJ; Watson, G; Schneider, A; Mackey, DA; Grigg, JR; Zenker, M; Jamieson, RV
Abstract : Ng WY, Pasutto F, Bardakjian TM, Wilson MJ, Watson G, Schneider A, Mackey DA, Grigg JR, Zenker M, Jamieson RV. A puzzle over several decades: eye anomalies with FRAS1 and STRA6 mutations in the same family. Fraser syndrome (FS) and microphthalmia syndromic 9 (MCOPS9) are autosomal recessive conditions with distinct, and some overlapping features affecting the ocular, respiratory and cardiac systems. Mutations in FRAS1 and FREM2 occur in FS, and mutations in STRA6 occur in MCOPS9. We report two sibships, in the same family, where four deceased offspring had ocular, respiratory and cardiac abnormalities. Two sibs with microphthalmia had syndactyly and laryngeal stenosis, suggesting a clinical diagnosis of FS. Our results indicate that they were compound heterozygotes for novel FRAS1 mutations, p.Cys729Phe and p.Leu3813Pro. The other two sibs, first cousins to the first sib pair, had anophthalmia, lung hypoplasia and cardiac anomalies, suggesting a retrospective diagnosis of MCOPS9. Our results indicate compound heterozygous STRA6 mutations, a novel frameshift leading to p.Tyr18* and a p.Thr644Met mutation. The one surviving individual from these sibships is heterozygous for the p.Tyr18* STRA6 mutation and has bilateral ocular colobomata and microphthalmia. This work emphasises the need for careful phenotypic characterisation to determine genes for assessment in ocular syndromic conditions. It also indicates that heterozygous STRA6 mutations may rarely contribute to microphthalmia and coloboma.